An exploration of whether a foreign language background impacts on the ability of Year 1 children in a British international primary school to assimilate English phonics skills and how this affects their reading development. ‘Everyone smiles in the same language’ (Unknown) - Dorkin, Debra-Anne (2016)
This explorative case study investigates the impact of a foreign language background on Year 1 children’s ability to learn English phonics and develop reading skills in a British international primary curriculum. A review of the literature places this study in context with other research conducted in this field, and highlights areas of commonality between published material and practical issues investigated in this research. Data gathering was carried out using a range of quantitative and qualitative methods, which when analysed, led to the conclusion that different language backgrounds are unlikely to have a long-term impact on the ability of Year 1 children to acquire English phonics and reading skills, for a number of reasons. While foreign language children who enter Year 1 with little or no English will struggle initially in learning English phonics, total immersion at school in English, both socially and instructionally, should allow them to catch up with their peers by the end of the academic year. Children are likely to benefit from a cross-linguistic transfer of skills, especially those who are bilingual in both English and another language; in fact an extension of Cummins’ common underlying proficiency model is proposed to take into account the cognitive benefits of continued exposure to another language. An original analogy is introduced to illustrate the interdependence of different skills necessary for the successful learning of phonics and development of reading. Recommendations are made for improving teaching and learning in the current setting and ways in which this research could be extended are suggested.